POTENSI PENERAPAN PRODUKSI BERSIH DI PETERNAKAN SAPI PERAH CV. MARGO UTOMO KECAMATAN KALIBARU KABUPATEN BANYUWANGI - Elida Novita; Ida Bagus Suryaningrat; Ega Daniati (Faculty of Agricultural Technology, University of Jember, 2018)
CV Margo Utomo dairy farm has approximately 99 cows. Livestock activities include feeding, cage cleaning, milking and livestock bathing. High feed and water requirements resultes high amounts of waste feed and waste produced. If wastewater discharged into channel, it could cause water pollution and could reduce environment. There were two types of waste water. The wastewater that disposed directly wastewater in to channel and the wastewater that settled in basin for three days. Steps of this research included field observation, secondary and primary data collection, problem identification, clean production alternatives identification, feasibility analysis and alternative selection based on priority scale of alternative clean production actions. Feasibility analysis includes technique, environment and economy. Assessment of feasibility based on assessment indicators in the form of questionnaires. This study used NPV, IRR, B / C Ratio, and PBP. There were three alternatives based clean production, that could be applied at the CV. Margo Utomo, such as biogas, water recycle , and cleaning pool for cows. Based on these alternatives, biogas was a best priority to applied in the CV. Margo Utomo dairy farm. Keywords: biogas, clean production, dairy farm, wastewater